2019
DOI: 10.1016/j.crci.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of antifungal colloidal copper nanoparticles and their antifungal activity against Fusarium oxysporum and Phytophthora capsici

Abstract: Copper nanoparticles (CuNPs) possess a promising antibacterial and antifungal activity with low-cost reagent and fabrication. In this study, we report the antifungal activity of pure CuNPs against Fusarium oxysporum (F. oxysporum) and Phytophthora capsici (P. capsici). CuNPs were prepared by reducing Cu 2þ from copper(II) chloride dihydrate via a green chemical reduction agent using ascorbic acid as both reducing agent and antioxidant agent in aqueous media and polyvinylpyrrolidone as a stabilizer. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…In this case, the PVDF-HFP coating has low values of surface free energies due to the presence of fluoride functional groups [ 59 ]. A previous work has shown that this value is around 10 mN·m −1 [ 60 ], although this surface energy value strongly depends on the content of HFP in the PVDF-co-HFP because it is associated to an increase in the fluorine content in the polymer [ 61 ]. In Figure 12 , the FTIR spectrum of the PVDF-co-HFP electrospun fibers is shown.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the PVDF-HFP coating has low values of surface free energies due to the presence of fluoride functional groups [ 59 ]. A previous work has shown that this value is around 10 mN·m −1 [ 60 ], although this surface energy value strongly depends on the content of HFP in the PVDF-co-HFP because it is associated to an increase in the fluorine content in the polymer [ 61 ]. In Figure 12 , the FTIR spectrum of the PVDF-co-HFP electrospun fibers is shown.…”
Section: Resultsmentioning
confidence: 99%
“…Cu NPs can particularly be considered to be a promising fungicide against P. capsici. Pham et al [ 47 ] reported that the colloidal solution of Cu NPs showed superiority in growth inhibition over P. capsici. The particle size of Cu NPs significantly affected their antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
“…There are several experiments on using Fusarium oxysporum fungus to synthesise nanoparticles in several experiments, including many studies on AgNPs. Srivastava et al synthesised AgNPs (10-15 nm in size) using fungus Fusarium oxysporum [67], and demonstrated promising antibacterial effects on Escherichia coli and Pseudomonas aeruginosa. Other examples of nanoparticles produced using F. oxysporum include copper [68], gold [69] and magnesium oxide [70].…”
Section: Fungimentioning
confidence: 99%